2006
DOI: 10.1002/ps.1276
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the impact of conventional pesticide and use of a transgenic pest‐resistant crop on the beneficial carabid beetle Pterostichus melanarius

Abstract: The potential impact of a chemical pesticide control method has been compared with that of transgenic plants expressing a protease inhibitor conferring insect resistance by utilising a tritrophic system comprising the crop plant Brassica napus (L.) (Oilseed rape), the pest mollusc Deroceras reticulatum (Müller) and the predatory carabid beetle Pterostichus melanarius (Illiger). Cypermethrin, as the most widely used pesticide in UK oilseed rape (OSR) cultivation, was selected as the conventional treatment. OSR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Due to successful introduction of genes coding for Bt toxins against insect pests in important crops such as cotton, maize and potato (AGBIOS, 2009), R&D activities in GM Brassica species toward insect resistance traits have been forced in recent years. In cabbage and oilseed rape, the expression of Bt toxins (Jin et al, 2000;Liu et al, 2008), harmful enzymes (Wang et al, 2005;Mulligan et al, 2006) and the regulation of insect gene expression through RNA interference (RNAi) (Baum et al, 2007) have been addressed. However, insect-resistant GM Brassica crops are not commercially available so far.…”
Section: Includementioning
confidence: 99%
See 1 more Smart Citation
“…Due to successful introduction of genes coding for Bt toxins against insect pests in important crops such as cotton, maize and potato (AGBIOS, 2009), R&D activities in GM Brassica species toward insect resistance traits have been forced in recent years. In cabbage and oilseed rape, the expression of Bt toxins (Jin et al, 2000;Liu et al, 2008), harmful enzymes (Wang et al, 2005;Mulligan et al, 2006) and the regulation of insect gene expression through RNA interference (RNAi) (Baum et al, 2007) have been addressed. However, insect-resistant GM Brassica crops are not commercially available so far.…”
Section: Includementioning
confidence: 99%
“…To what extent insect resistance as a newly introduced trait interferes in multitrophic relationships between the host plant, insect pests and their parasitoids has specifically been studied in gene-modified B. napus expressing the Bt toxin, with negligible effects on beneficial species (Schuler et al, 2001(Schuler et al, , 2004Ferry et al, 2006;Mulligan et al, 2006). Recent studies on the glucosinolate content and composition of host plants with differing insect resistance potential have shown that changed plant chemistry possibly impairs parasitoid fitness, underscoring how fine-tuned evolutionary-developed plant herbivoreparasitoid interactions are (Gols et al, 2008b;Bukovinszky et al, 2009;Hopkins et al, 2009).…”
Section: Includementioning
confidence: 99%
“…Thus, the accusation that we recognize no non-neutral effects of genetically modiÞed (GM) crops is false, and we did not make such a claim in Shelton et al (2009). In addition, several of the authors have worked extensively with proteinase inhibitors (PIs) and lectins and have documented many non-neutral effects of these more broad-spectrum proteins (Burgess et al 1996;Malone et al 2000;Bell et al 2001a, b;Ferry et al 2003Ferry et al , 2005Romeis et al 2003;Hogervorst et al 2006;Mulligan et al 2006;Li and Romeis 2009). Our concern was and continues to be focused on the limitations of the meta-analysis performed by Lö vei et al (2009).…”
Section: As We Described In Our Rebuttal In Transgenic Researchmentioning
confidence: 88%
“…Predators of the families Carabidae and Dermaptera were affected by the pest management strategies with higher densities in IPM than farmers’ practices plots. Broad‐spectrum insecticides affect carabids at normal application rates (Mulligan et al., ). These findings are in accordance with the results of our study on the efficacy of selective versus broad‐spectrum insecticides for controlling the leafminer fly, in which broad‐spectrum insecticides reduced nearly 50% of the total predator and 82% of the carabid density compared with untreated and selective insecticide‐treated potato plots (Mujica, ).…”
Section: Discussionmentioning
confidence: 99%